Design, synthesis and biological evaluation of novel kojic acid triazole hybrids as tyrosinase inhibitors and antibrowning agents - Dan Liu; Junyuan Tang; Sheng Tao; Dahan Wang; Jinbing Liu (Scientific Reports)
Abstract In this study, two series of kojic acid triazole hybrids, namely 6a–6p and 13a–13t, were designed and synthesized. Subsequently, their biological activities including anti-tyrosinase, antioxidant, and as anti-browning effects were investigated. The results showed that most of compounds demonstrated excellent inhibitory effect against mushroom tyrosinase compared with standard reference drug (kojic acid, IC50 = 26.090 µM). Of particular note, 13t proved to be the most potent tyrosinase inhibitor with an IC50 value as low as 1.363 µM. Further kinetic inhibition studies suggested that 13t presented such powerful anti-tyrosinase efficacy by functioning as a mixed-type inhibitor (K i = 0.3647 µM, K is = 0.8492 µM). Moreover, the results from molecular docking and fluorescence quenching studies revealed that 13t’s inhibitory effect on tyrosinase stemmed from its ability to directly bind to the active site of mushroom tyrosinase. Besides, the antioxidant activity, anti-browning effect, and cytotoxicity of 13t were accordingly investigated, all yielding highly satisfactory results. Collectively, these findings position 13t as a highly promising candidate, providing a valuable molecular framework for the development of novel, efficient, and safe tyrosinase inhibitors endowed with potent antioxidant and anti-browning capabilities.